Implementation of Story-Based Tajwid Ahmad Learning Method in Islamic Boarding Schools - A, Ahmad; Getteng, Abd Rahman; Djollong, Andi Fitriani; Halik, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study examines the implementation of the story-based Tajwid Ahmad learning method at the Miftahul Jihad Tande Islamic Boarding School, East Banggae District, Majene Regency, West Sulawesi. This research uses a qualitative approach with philosophical, theological-normative, pedagogical, psychological, and sociological foundations. Data was obtained through observation, in-depth interviews, and documentation, with data analysis techniques that include data reduction, data presentation, verification, and conclusions drawn. The study results show that Tajwid learning with Ahmad's story approach can increase students' understanding, emotional involvement, and love for the Qur'an. The main obstacles in learning include limited facilities, teaching materials, and time allocation. However, the role of a patient and inspirational ustad is the key to building the motivation and confidence of students. The story-based method provides a more lively and contextual learning atmosphere. This research implies that a simple learning approach that touches on emotional and pedagogical aspects can be an effective solution in an Islamic boarding school environment with technological limitations. Ongoing support, both in terms of facilities and training of educators, is needed to strengthen the implementation of this method in the long term. This experience can be an alternative model in developing Tajwid learning that is more humanistic and applicative.